Design of multifunctional titania-based photocatalysts by controlled redox reactions - Lopes, Diogo João Breda (2019)
This work was focused on designing the phase composition and microstructure of composite rutile – silicon carbide mixture by controlled redox reactions, aiming the preparation of multifunctional titania-based photocatalysts with inherent capabilities for thermal co-activation and stabilization of the anatase polymorph. The materials were processed using a conventional solid state route, involving a partial reduction of the rutile by SiC in inert Ar atmosphere, followed by the post-oxidation in air. The impacts of processing conditions on the phase composition of the oxidized samples and their photocatalytic activity were evaluated using Taguchi experimental planning. The XRD studies confirmed the presence of rutile/anatase mixtures in the oxidized samples. The results emphasized that the pre-reduction and post-oxidation temperatures are the most critical parameters in defining the phase composition, while the post-oxidation time appears to be relevant for the photocatalytic performance. Microstructural studies revealed the formation of core-shell particles in the pre-reduced and post-oxidized samples, which can suppress the photocatalytic activity. The highest apparent reaction rate (0.089 min-1) of the photodegradation of methylene blue was observed for the sample pre-reduced in Ar at 1300ºC for 5 h and then oxidized in air at 400ºC for 25 h, which is only 1.6-times lower than that for nanostructured industrial P25 photocatalyst, tested under the same conditions. The observed trends demonstrate good prospects for designing multifunctional titania-based photocatalysts based on the flexibility of the phase composition control